Brand equity: Does the brand name and/or price affect perceptions of quality? - Hilgenkamp, Heather (Kansas State University, 2009)
This project included two studies that looked at how the brand name and price of consumer products can affect intended purchasing decisions. In Study 1, 30 undergraduate students tested products from three different product categories (crayons, tissues, and tortilla chips). Each product category consisted of three different brands; one with high brand value, one with medium, and one with low brand value (generic). The brands for each product were as follows: Crayons (Crayola, Roseart, and Dollartree); Tissues (Puffs, Kleenex, and Wal-Mart); Chips (Tostitos, Mission, and Kroger). The design for this study was a 3x3+3+3 matrix. For each brand, there were five conditions: 1) the product in the correct brand name; 2) the product in a switched brand name; 3) the product in the other switched brand name; 4) the product alone, no brand name; and 5) the brand name alone, no product. The product alone and brand name alone conditions acted as controls. Participants were unaware that the products had been switched. After trying each product, participants rated their likelihood to purchase that product on a 9-point Likert scale; 1 being “definitely would not buy” and 9 being “definitely would buy.” In Study 2, 47 participants completed an online survey assessing their likelihood to purchase three different products (a bicycle, a watch, and a T.V.) based on the price alone. The brand names were removed so as to not create an interactive effect. This study had the same design as Study 1. After a within-subjects Repeated Measures ANOVA, it was found in Study 1, that the two brands with higher brand value were rated as higher quality than the generic. Study 2 found that when just looking at price, subjects were more likely to purchase the cheapest product. In conclusion, it seems that the brand name associated with a product can cause people to rate the quality of that product as either higher or lower depending on the strength of the brand, even if the product itself is lower quality. Also, when looking at the prices of products without the brand names, people want to purchase the lowest priced product.
Keywords: Brand Equity; Brand Name; Price; Consumer Psychology; Business Administration, Marketing (0338); Psychology, Cognitive (0633)